Research involvement among undergraduate health profession students in a resource‑limited setting: awareness, attitude, motivators and barriers - Kiyimba, Blaise; Atulinda, Linda; Nalunkuma, Racheal; Asasira, Ignatius; Kabunga, Jonathan; Banturaki, Davis; Nabyonga, Anastacia S.; Nakiganda, Rachel; Ndyabawe, Rachael; Nkalubo, Jonathan; Ssewante, Nelson; Bongomin, Felix; et al. (BMC Medical Education, 2022)
Involvement of undergraduate health professions students (HPS) in research will facilitate evidencebased clinical practice among future healthcare practitioners. This study aimed to assess research involvement among undergraduate HPS students and associated factors in Uganda. Methods: A cross-sectional study was conducted using an online assessment tool sent through WhatsApp groups and E-mail addresses of HPS in 12 medical schools in Uganda between 20th September and 5th October 2021. Results: We enrolled 398 participants with a mean age of 23.9 ± 3.7 years. Of this, 267 (67.1%) were male. One hundred twenty (30.2%) participants previously participated in a research activity: 90 (58.4%) as research assistants, 39 (25.3%) published as first authors, and 25 (16.2%) as co-authors. Training on the conduct of research was received by 242 (65.8%) participants, and 326 (81.9%) had intentions of conducting research in the future. Factors influencing participation in research activities were, age ≥ 25 years (adjusted odds ratio (aOR): 1.9, 95% confidence interval (95% CI): 1.2–3.2, p = 0.012), being male (aOR: 2.1, 95%CI: 1.2–3.6, p = 0.008), and being in a clinical year i.e., year 3 (aOR: 3.2, 95% CI: 1.1–9.3, p = 0.033), year 4 (aOR: 3.3, 95% CI: 1.1–9.5, p = 0.028) and year 5(aOR: 11.6, 95% CI: 3.2–42.1, p < 0.001). Lack of funds (79.6%), and mentorship (63.3%) were reported as major barriers to research. Conclusions: Despite a high proportion of HPS showing interest in getting involved in research, less than one-third reported previous involvement. Addressing barriers such as funding could potentially improve research involvement and output among undergraduate HPS in resource-limited settings.